Front Cover: Crystalline Metal‐Peptide Networks: Structures, Applications, and Future Outlook (ChemBioChem 2/2023). (14th November 2022) - Jeong, Seoneun; Lee, Kwonjung; Yoo, Sung Hyun; Lee, Hee‐Seung; Kwon, Sunbum
Abstract : Crystalline metal‐peptide networks (MPNs) constructed from coordination‐driven self‐assembly of metal ions and peptidic ligands display distinctive 2D or 3D reticular architectures. MPNs have attracted much attention due to their potential for development of versatile materials, but there are several underlying hurdles to be addressed for practical applications. In this review, we introduce various examples of MPNs with comprehensive descriptions of their structural characteristics and discuss future perspectives. More information can be found in the Review by H.‐S. Lee, S. Kwon et al.